Production of eggplant seedlings in substrate conditioned with Biochar - Marimon Junior, Ben Hur; Petter, Fabiano André; Andrade, Fabricio Ribeiro; Madari, Beáta Emöke; Marimon, Beatriz Schwantes; Shossler, Thiago Rodrigo; Gonçalves, Laissa Gabriele; Belém, Rodrigo (Comunicata Scientiae, 2012)
In present study we evaluated the effects of fine charcoal (biochar) previously treated with water and acids, with different substrates in the formation of eggplant seedlings. The experiment was carried at the University of Mato Grosso, in Nova Xavantina county, Mato Grosso state, Brazil. The experimental design was randomized blocks in factorial 3 x 4, with factors consisting of three treatments of the substrate (compost of cotton waste, Oxisol (land) + sawdust and Oxisol (land) + cattle manure) associated with 0% (control) and 40% of biochar with three different types of chemical activation for biochar (water, sulfuric acid and nitric acid) were used, with four replications. At 55 days after sowing (DAS) was evaluated the number of true leaves, root length, diameter and stem length, plant height and fresh and dry weight of shoot. The results showed that highest number of leaves occurred with substrate utilization of soil + cattle manure in the presence of HNO 3- treated with biochar. The highest root length was found associated with composite cotton to 40% of biochar treated with H2SO4-. The shorter length and diameter were recorded using the substrate soil + saw-dust associated with biochar independent of the chemical treatment used. The use of land associated with cattle manure + 40% HNO3- treated with biochar showed the highest values of fresh and dry weight. Generally not recommended to use the substrate soil + saw-dust with or without biochar for the production of eggplant seedlings.